Seating arrangements ebook - Shipstead, Maggie (2012)
NATIONAL BESTSELLER • Winner of the Los Angeles Times Book Prize • The irresistible story of a summer New England wedding weekend gone awry—a deliciously biting satirical glimpse into the lives of the well-bred and ill-behaved, f rom the New York Times bestselling author of Great Circle. The Van Meters have gathered at their family retreat on the island of Waskeke to celebrate the marriage of daughter Daphne—seven months pregnant—to the impeccably appropriate Greyson Duff. The weekend is full of champagne, salt air and practiced bonhomie, but long-buried discontent and simmering lust stir beneath the surface. Winn Van Meter, father of the bride, is not having a good time. Barred from the exclusive social club he’s been eyeing since birth, he’s also tormented by an inappropriate crush on Daphne’s beguiling bridesmaid, Agatha, and the fear that his daughter, Livia—recently heartbroken by the son of his greatest rival—is a too-ready target for the wiles of Greyson’s best man. When old resentments, a beached whale and an escaped lobster are added to the mix, the wedding that should have gone off with military precision threatens to become a spectacle of misbehavior.